ممتازاطہر کی شاعری: فکری وفنی مطالعہ: MUMTAZ ATHAR'S POETRY: AN INTELLECTUAL AND ARTISTIC STUDY (Al-Aasar, 2026)
Mumtaz Ather holds a prominent position in the poetic tradition of Multan. To express his thoughts, he adopted the genre of Ghazal alongside other forms of poetry. While he has published four poetic collections to date, he maintains a distinct identity among the poets of Multan due to his unique style and innovative approach.Mumtaz Ather is always in search of new creative possibilities and possesses a constant drive to move forward without stagnating at any single point. The brilliance of his Ghazal writing fully emerged during the 1970s. The prominent theme in Mumtaz Ather’s poetry is resistance. In his work, resistance stems from his contemporary awareness and the profound impact of the prevailing political climate.The experiences reflected in his poetry are not merely derived from books; rather, they are the fruit of his arduous journey through the "deserts of life." Mumtaz Ather beautifully transforms the political and social realities of his era into the core subjects of his poetic expression.